Surgical Techniques in Rectal Cancer Transanal, Laparoscopic and Robotic Approach (Springer Japan, 2018)
This book describes the various procedures, including surgery through the abdominal wall, through a transanal access or by the union of both, using an open, laparoscopic, or robotic approach. Worldwide pioneers for each technique are invited as authors and portray in step-by-step detail about each procedure. Of the 32 chapters, 23 are dedicated only for the surgical procedures. Each chapter is enriched by numerous figures, which complement the text, permitting the understanding of each surgical technique from its beginning until the last step. Eight additional chapters are dedicated to the clinical and anatomical aspects of rectal cancer. In the last decade there has been an impressive evolution in the treatment of patients with rectal cancer, with a focus not only on the preservation of a cancer-free life, but the quality of that life. This book has been written to be useful for everyone involved in rectal cancer management. From internists, gastroenterologists, endoscopists, oncologists, radiotherapists and radiologists involved in the treatment of rectal cancer during their daily practice, to surgeons specialized in colorectal surgery, to junior faculty to trainees, all interested in new and innovative techniques.